1990
DOI: 10.1524/ract.1990.51.3.97
|View full text |Cite
|
Sign up to set email alerts
|

Mass Distribution of Fission Products from Moderately Excited 236U Compound Nucleus

Abstract: The chain yields of 30 fission products were determined in 38 MeV a-particle induced fission of ^'^Th. The mass yield curve was found to be primarily asymmetric with a peak to Valley {pj v) ratio of 3.5. A small peak has also been observed in the Symmetrie region. The observed pjv ratio has been resolved into the pjv ratios of the individual mass distributions of the possible fissioning isotopes of uranium formed as a result of multichance fission. An attempt has been made to explain the pjv ratios thus obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
3
5
0
Order By: Relevance
“…The asymmetric mass distribution at each energy shows a peak corresponding to the symmetric region which gradually becomes more prominent at the higher excitations. Similar peaks and also similar yield-mass distribution were observed by Roginski et al [2] upto the incident beam energy of 41 MeV and by Guin et al [4] at 38.5 MeV.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…The asymmetric mass distribution at each energy shows a peak corresponding to the symmetric region which gradually becomes more prominent at the higher excitations. Similar peaks and also similar yield-mass distribution were observed by Roginski et al [2] upto the incident beam energy of 41 MeV and by Guin et al [4] at 38.5 MeV.…”
Section: Resultssupporting
confidence: 86%
“…The dots denotes the reflected points. The data of Guin et al [3,4] are denoted by triangles. The typical error in the experimental data are around 20%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kudo et al [1] have observed the asymmetry in the mass division in the proton induced fission of 232 Th up to energies of 21 MeV and that the peak to valley ratio (P/V) decreases with increasing excitation energy. Similar observations were made in the α particle induced fission of 232 Th [2,3] at 28.5 and 38.5 MeV. On the other hand the mass distributions in the α particle induced fission of 233 U [4], 238 U, 237 Np [5] and 239 Pu [6] at excitation energies of the order of 35 MeV or more are symmetric.…”
Section: Introductionsupporting
confidence: 81%